2009
DOI: 10.12681/mms.118
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory and ion transport potential of Penaeus japonicus gills in response to environmental pollution

Abstract: The present study aims to pinpoint the respiratory and ion transport potential of gills of Penaeus japonicus living in Abu-Qir Bay, East of Alexandria, Egypt. Our results revealed clear histological impairments in gill structure. These alterations were mainly represented by the presence of large vacuoles in gill axis and gill lamellae. In addition, narrow, disrupted gill lamellae with wavy cuticle and shrunk pillar cells were detected. Moreover, some cells clearly showed pyknosis. Gill ultrastructure also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Na + -K + -ATPase is an ion channel that uses the energy generated by ATP hydrolysis to maintain membrane potential by driving three Na + outlets and two K + intents, which is essential to osmotic regulation (Evans and Lambert, 2015;Abdel-Mohsen, 2016). In this study, after 12 h and 24 h of salinity stress, Na + -K + -ATPase activity of P. fucata with black shell in low-salt and high-salt groups was significantly lower than that in the control, showing an inverted U-shape distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Na + -K + -ATPase is an ion channel that uses the energy generated by ATP hydrolysis to maintain membrane potential by driving three Na + outlets and two K + intents, which is essential to osmotic regulation (Evans and Lambert, 2015;Abdel-Mohsen, 2016). In this study, after 12 h and 24 h of salinity stress, Na + -K + -ATPase activity of P. fucata with black shell in low-salt and high-salt groups was significantly lower than that in the control, showing an inverted U-shape distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that following RT‐PCR and phosphorImaging analysis, G6PD transcript in a salinity of 6‰ was down‐regulated compared with 12‰ of Sparus sarba (Deane & Woo, 2005). L‐lactate dehydrogenase (LDH) is a key enzyme in the glycolytic pathway and the tricarboxylic acid cycle, and its activity can be used as an indicator of anaerobic metabolism (Abdel‐Mohsen, 2009). In this study, LDH in the LS group was significantly down‐regulated compared with the HS group after overwintering.…”
Section: Discussionmentioning
confidence: 99%
“…SDH plays a key role in the TCA cycle and also is involved in oxidative phosphorylation, so the activity of SDH can reflect the level of aerobic metabolism to some extent (Metón, Fernández & Baanante ). LDH is closely related to cell metabolism and is a key enzyme in glycolysis and the TCA cycle; thus, its activity can be used as a measure of the level of anaerobic metabolism (Valarmathi & Azariah ; Abdel‐Mohsen ). Under red and white light at 4L:20D and 8L:16D, the SDH activity was higher than that under blue light, which suggests that these light qualities and cycles provided a good environment characterized by little stress and energy supplied primarily through aerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%